Avaliação dos fatores que influenciam na percepção de risco de inundação: uma revisão sistemática de pesquisas empíricas - Murilo Noli da Fonseca; Carlos Mello Garcias; Luciene Pimentel da Silva (Confins)
Knowing the main factors that influence the degree of flood risk perception of the various actors of an urban system is fundamental to enable behavioral changes and the development of more effective measures to reduce risk and preparedness in the face of the occurrence of a flood. This research aims to evaluate the factors that influence the degree of perception of flood risk in the promotion of assertive actions for adaptation and mitigation of climate change. The methodology involves a systematic review of the literature as a research technique. The studies highlight a trend that respondents with older age, more experience of flooding, higher awareness, lower monthly income, lower schooling and less confidence in the government presented greater perception of risk. In addition, they indicate significant deficiencies in current understandings, highlighting the scarcity of evidence for the relationship between risk perceptions and mitigation behavior, and a failure to make use of theoretical structures in research. It is suggested as a strategy in risk management that it should be adapted to different population groups, considering the characteristics and needs of each of them.